2017
DOI: 10.1016/j.bbmt.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Utility of Relapse Surveillance after Allogeneic Hematopoietic Cell Transplantation in Children with Leukemia

Abstract: The utility and optimal timing of routine bone marrow (BM) and cerebrospinal fluid (CSF) surveillance after allogeneic hematopoietic cell transplantation (alloHCT) in children with leukemia have not been previously studied. To examine the current practice concerning relapse surveillance in this population, we conducted a national survey of pediatric bone marrow transplant physicians. Sixty-two of 152 potential participants (41%) completed the survey. For acute lymphoblastic leukemia (ALL) patients, 41 physicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…25 A separate survey showed that 41% of physicians report using posttransplant intrathecal chemotherapy in pediatric patients. 26 Physicians perform post-transplant lumbar punctures in 55% of children with ALL, though only 3.5% in AML patients. 26 Although considered to be a safer alternative than radiation therapy, intrathecal chemotherapy is not without risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 A separate survey showed that 41% of physicians report using posttransplant intrathecal chemotherapy in pediatric patients. 26 Physicians perform post-transplant lumbar punctures in 55% of children with ALL, though only 3.5% in AML patients. 26 Although considered to be a safer alternative than radiation therapy, intrathecal chemotherapy is not without risk.…”
Section: Discussionmentioning
confidence: 99%
“…26 Physicians perform post-transplant lumbar punctures in 55% of children with ALL, though only 3.5% in AML patients. 26 Although considered to be a safer alternative than radiation therapy, intrathecal chemotherapy is not without risk. Intrathecal methotrexate has been associated with rare side effects including seizures, stroke-like symptoms, and encephalopathy; neurologic toxicities appear similar whether methotrexate is given alone or in combination with cytarabine and hydrocortisone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 reported their experience with early withdrawal of IS and the use of fresh whole blood DLI to mitigate relapse of leukemia and prevent graft rejection after HCT in children with mixed chimerism, transplanted for benign diseases or leukemia. In total, 58 patients received DLI, in an escalating dose regimen with CD3 + cell/kg as follow: 1x10 5 (or 10 4 for haploidentical recipients), 5×10 5 and 1x10 6 , depending on the graft kinetics and the clinical status of the children.…”
Section: Preemptive Post-hsct Interventions Based On Mrd and Chimerism Kineticsmentioning
confidence: 99%
“…4 Relapse incidence (RI) following transplantation varies from 13 to 47%, depending on patient, disease and transplant features, while the incidence of CNS relapse, the most common site of extramedullary relapse, varies from 3.9 to 9.4% for patients without or with prior CNS disease, respectively. 5,6 In Brazil, two recent retrospective multicenter studies evaluated outcomes in pediatric patients and observed lower OS rates compared to higher-income countries. Tavares and cols.…”
Section: Introductionmentioning
confidence: 99%